An Analysis of Leadership: Enhancing Pedagogy for Teachers at Al Mawasir Lamasi Islamic High School - Liswanto Loncing; Hisban Thaha; Muhaemin Muhaemin (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
This research explores the Madrasah Head's leadership role in enhancing teachers' pedagogical competence at Madrasah Aliyah Al Mawasir Lamasi, including various leadership styles and their impact. It also identifies supporting and inhibiting factors. This research employs a qualitative descriptive approach to objectively describe facts or phenomena by collecting data as they exist during the research process. The study was conducted at MA Al Mawasir Lamasi, located on Poros Lamasi Street, Lamasi District, Luwu Regency. The research subjects comprised 25 individuals, including the Head of the Madrasah, Vice Principals, and MA Al Mawasir Lamasi teachers. This study utilized three main data collection techniques: observation, interviews, and documentation. Based on the research results that involved data, interviews, observations, and documentation, as well as the analysis conducted, it is evident that the pedagogical competence of teachers at Madrasah Aliyah Al Mawasir Lamasi has been effectively implemented following the applicable competency standards. Implementing pedagogical competence encompasses mastery of instructional materials, understanding student characteristics, development of relevant curriculum, delivery of quality teaching, precise student assessment and evaluation, and utilizing information and communication technology as a supporting tool in the learning process